Asuhan Kebidanan Komprehensif Pada Ny. N Dengan Obesitas: (Studi Kasus Terhadap Ny. N di Puskesmas Jatibogor Kabupaten Tegal) - Tivani Putri; Istiqomah Dwi Andari; Riska Arsita (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
AKI worldwide according to WHO in 2018, namely 108,300 In Indonesia, AKI cases in 2020, namely 6,856. In Central Java, MMR in 2021 is 1,011 with Tegal Regency at 29.78% and IMR 48 cases. Data at the Jatibogor Health Center for obesity cases total of 16 pregnant women. Obesity is a condition of conflict between body weight and height due to excess fat tissue in the body. The incidence rate of overweight or obesity is increasing over time, even one of which became a global pandemic with a prevalence of 2.1 billion in 2013, an increase from 857 million cases in 1980. Obesity can be assessed from the body mass index (BMI), which World Health Organization (WHO) classifies obesity as BMI≥ 30 kg m2. Obesity generally occurs in pregnancy, especially pregnancies that occur over 35 years. This state of obesity is a high risk obstetrics because it can increase the risk of morbidity and mortality of the mother and fetus. Complications that can occur in pregnant women with a risk of obesity in pregnant women are an increase in gestational diabetes hypertension, spontaneous abortion and postpartum hemorrhage. In the fetus it can increase the risk of stillbirth in the antepartum period, intrapartum complications such as shoulder dystocia, macrosomia and increase the risk of fetal defects such as neural tube defects, spina bifida, congenital heart disease and omphalocele. Macrosomia is a condition in which a baby is born with a larger size or a body weight of 4000 grams, this is one of the complications of childbirth which causes increased morbidity and mortality in pregnancy because it causes many complications in childbirth.